Entrepreneurial traits among university students in South Africa - Mhlanga, Sylvia Shingaidzo (University of the Witwatersrand, Johannesburg, 2021)
At a time when South Africa critically needs businesses categorised as small and medium-scale enterprises (SMEs) to contribute meaningfully to the economy, there is a gap in research undertaken on the levels of personality trait among youths in South Africa, specifically focusing on their related impact on new venture formation and entrepreneurial success. Anchored on the Psychological Entrepreneurship Theory, the research was aimed at examining whether university students possess the personality traits that influence new venture formation, as well as one’s success as an entrepreneur. Through examining their entrepreneurial traits, the study evaluated whether entrepreneurship is a viable career option for undergraduate university students and identified if existing policy interventions are adequate in addressing any entrepreneurial personality gaps among university students. The literature review section was targeted at highlighting some of the existing key research work on the interrelatedness of personality traits and entrepreneurship, as well as how each of the personality traits in the Big Five Model influence entrepreneurship. Utilising a questionnaire design consistent with the Big Five Approach, data was collected from 62 undergraduate students at the University of Witwatersrand, to assess the levels of their entrepreneurial personality traits. The data was statistically analysed, using mean scores and frequency distributions, to assess the levels entrepreneurial traits among undergraduate students and the results presented, including all policy recommendations and conclusions. Results of the internal factor validity tests conducted on each of the entrepreneurial traits using the Cronbach’s alpha showed that although the factors used in the questionnaire were generally valid, the research instrument could be improved by replacing the factors that had lower scores. Results of the significance tests on the variables showed that there was strong evidence of relationships between the entrepreneurial traits and demographic variables among the undergraduate students. The results of the study also showed that although there is a high level of entrepreneurial traits among undergraduate university students, some personality traits were less developed and needed further strengthening
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration, Johannesburg 2021
Keywords: Entrepreneurial; Personality traits; Big Five Model; Entrepreneurial intention; Entrepreneurial success; UCTD; SDG-4: Quality education